2012
DOI: 10.1021/cn200117j
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Kinase Inhibitors for LRRK2 and Their Application to Parkinson's Disease Models

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder. Several single gene mutations have been linked to this disease. Mutations in the gene encoding leucine-rich repeat kinase 2 (LRRK2) indicate LRRK2 as promising therapeutic target for the treatment of PD. LRRK2 mutations were observed in sporadic as well as familial PD patients and have been investigated intensively. LRRK2 is a large and complex protein, with multiple enzymatic and protein-interaction domains, each of which is effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 80 publications
2
35
0
Order By: Relevance
“…In line with our data, an in vivo study in LRRK2 mutant animals has suggested an involvement of LRRK2 in neurotransmitter release . Our data further suggest that this function of LRRK in flies is mediated by LRRK2 and not LRRK1 in the mammalian system, as LRRK2-IN-1 does not inhibit LRRK1 kinase function (Kramer et al, 2012). Future studies in LRRK1-knockout neurons could strengthen this hypothesis further.…”
Section: Discussionsupporting
confidence: 50%
“…In line with our data, an in vivo study in LRRK2 mutant animals has suggested an involvement of LRRK2 in neurotransmitter release . Our data further suggest that this function of LRRK in flies is mediated by LRRK2 and not LRRK1 in the mammalian system, as LRRK2-IN-1 does not inhibit LRRK1 kinase function (Kramer et al, 2012). Future studies in LRRK1-knockout neurons could strengthen this hypothesis further.…”
Section: Discussionsupporting
confidence: 50%
“…A large number of ATP competitive type I inhibitors of LRRK2 have been reported from screening studies and recently reviewed (21, 86, 87). In addition, homology models of LRRK2 built by other research groups have been used successfully to drive SAR studies for ATP-competitive inhibitors (88).…”
Section: Discussionmentioning
confidence: 99%
“…As the most common LRRK2 mutation (G2019S) augments kinase activity, development of LRRK2 kinase inhibitors has been proposed as a promising approach [156]. Many kinase inhibitors will block LRRK2 activity, with CZC-25146 and LRRK2-IN1 having high specificity for LRRK2 [157][158][159]. Neither of these kinase inhibitors would be taken into clinical trials owing to their poor blood-brain barrier permeability [159], although more recent inhibitors may be have better distribution in the brain [160][161][162].…”
Section: Therapeutic Strategies For Lrrk2-associated Pdmentioning
confidence: 99%